Safety and efficacy of second-generation all-suture anchors in labral tear arthroscopic repairs: prospective, multicenter, 1-year follow-up study - Andrew L. Wallace, MA, PhD, FFSEM, FRCS, FRACS; Emilio Calvo, MD, PhD; Jordi Ardèvol Cuesta, MD; Riccardo Lanzetti, MD; Gonzalo Luengo-Alonso, MD, PhD, FEBOT, ECFMG; Andrew S. Rokito, MD; Edwin E. Spencer, Jr, MD; Marco Spoliti, MD (JSES International, 2024)
Background: This study’s primary aim was to assess the safety and performance of second-generation all-soft suture anchors following arthroscopic labral tear repair. Methods: This prospective, multicenter study was conducted by 6 surgeons at 6 sites in Europe and the United States between November 2018 and August 2020. Patients who required shoulder arthroscopic repair, for a range of labral injuries, were treated with a second-generation all-soft suture anchor. The primary outcome was clinical success rate (percentage of patients without signs of failure and/or reintervention) at 6 months. Secondary outcomes included clinical success rate at 12 months, intraoperative anchor deployment success rate, and patient-reported outcomes (PROs) at 6 and 12 months, including visual analog scale (VAS) pain assessment, VAS satisfaction assessment, EQ-5D-5L Index Score, EQ-5D-5L VAS Health Score, Rowe Shoulder Score for Instability, American Shoulder and Elbow Surgeons score, and Constant-Murley Shoulder Score. Serious adverse events and serious adverse device effects were collected throughout the study. Results: Forty-one patients were enrolled (mean age, 28.2 years; 87.8% male, 12.2% female). Clinical success was achieved in 27/28 and 31/32 patients at 6 months and 12 months, respectively. Anchor deployment had a 100% success rate. Significant improvements over baseline were reported for all PROs except Constant-Murley Shoulder (6 months) and VAS Satisfaction Score (12 months). One patient experienced 1 serious adverse event and 1 patient experienced 1 serious adverse device effect. Conclusion: Second-generation all-soft suture anchors used in this study demonstrated a high clinical success rate, a favorable safety profile, and patients exhibited significant improvement in PROs.